2015
DOI: 10.1186/s12885-015-1658-2
|View full text |Cite
|
Sign up to set email alerts
|

High expression of AGR2 in lung cancer is predictive of poor survival

Abstract: BackgroundAnterior gradient 2 (AGR2) is a protein disulfide isomerase-like protein widely expressed in many normal tissues as well as cancers. In our study, non-neoplastic bronchial epithelial cells as well as non-small cell lung cancer (NSCLC) cells express AGR2 protein.MethodsAGR2 expression was analyzed on lung tissue microarrays. Tumor staining was correlated with clinical outcomes.ResultsOn a lung cancer tissue microarray using immunohistochemistry, expression levels in cancer showed generally decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
2
38
0
1
Order By: Relevance
“…clearly up-regulated in LUSC, entailing a promising marker to discriminate the two lung cancer types. Another interesting candidate is AGR2, which has been associated with lung cancer, as a prognostic marker [98][99][100]. Our results point to an up-regulation of AGR2 in LUAD, consistently with the findings in literature and down-regulation in LUSC.…”
Section: Candidate Genes In Lung Cancer and Other Cancer Typessupporting
confidence: 90%
“…clearly up-regulated in LUSC, entailing a promising marker to discriminate the two lung cancer types. Another interesting candidate is AGR2, which has been associated with lung cancer, as a prognostic marker [98][99][100]. Our results point to an up-regulation of AGR2 in LUAD, consistently with the findings in literature and down-regulation in LUSC.…”
Section: Candidate Genes In Lung Cancer and Other Cancer Typessupporting
confidence: 90%
“…19 Recently, anterior gradient protein-2 (AGR2), an androgen-regulated gene, has been identified as an oncogene and generally overexpressed in various cancers. [20][21][22][23] AGR2 promotes the metastasis of breast cancer cells. 21 Besides, High AGR2 expression has been reported to show lower overall survival of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, AGR2 expression has been observed relatively high in prostate cancer and lung cancer. 20,23 It has been reported that AGR2 is a direct target of miR-342-3p. 13 In our study, LINC00460 was proved to mainly distribute in the cytoplasm, thus regulating the post-transcription of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…AGR2 expression was shown to be significantly increased in HER2 positive breast tumors [147]. High levels of AGR2 were also associated with cell dissemination of pancreatic carcinoma [148] and with poor prognosis of lung cancer [149]. Worth of note, this protein appears highly represented in the tumor tissues (when present) and almost absent in the normal ones.…”
Section: Anterior Gradient Protein 2 Homolog Agr2 (Agr2)mentioning
confidence: 97%